THE INFLUENCE OF TREATMENT FREQUENCIES USING NECTAR FLORA HONEY TOWARDS SECOND DEGREE’S BURN ON WOUND HEALING DURATION - Dewi SLI, Dina; Sanarto, Sanarto; taqiyah, Barotut (University of Muhammadiyah Malang, 2011)
One of them is used as the properties of wound healing. Many research has been done, include the use of honey on treatment of secon degree’s burn. In those research are lack of consensus on how often to apply honey. It is varies from every two days, once daily, twice daily, and three times daily.Because of that, this research want to answer that question so we can know how often the treatment of second degree’s burn using honey should be applied. This research is conducted to test and to know the influence of treatment frequency on second degree’s burn using honey to quicken wound healingduration and to know which frequency has the best result on quickening wound healing. This research is true experiment study with pretest-postest control group design system. 20 cavia porcellus, as samples, are divided into 5 groups: 1) contol group; 2) second degree’s burn care group with honeyapplied every to days; 3) second degree’s burn care group with honey applied once daily; 4) second degree’s burn care group with honey applied twice daily; 5) second degree’s burn care group with honey applied three times daily. Assessment of wound is applying every day using wound assesmentform in wound manajement by Morison Moya. Means of wound healing in control group is 14,5 days, group 2 is 13,5 days, group 3 is 11,75 days, group 4 is 10,5 days, and group 5 is 10 days. One way anova test shows the differences of wound healing means between each group is significant with Fcount (6,992) > F table (3,06) and p < α 0,05. LSD says there are no significant difference between group 3, group 4, and group 5. But the difference between group 4 and group 5 shows the highest significant value (p = 0,634), so it can conclude that the group 5 has the most same effects on group4. The treatments of second degree’s burn using honey twice daily and three times daily are better than those done every two days and once daily.